Adenosine monophosphate-activated protein kinase in diabetic nephropathy - Yaeni Kim; Cheol Whee Park (The Korean Society of Nephrology, 2016)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease, and its pathogenesis is complex and has not yet been fully elucidated. Abnormal glucose and lipid metabolism is key to understanding the pathogenesis of DN, which can develop in both type 1 and type 2 diabetes. A hallmark of this disease is the accumulation of glucose and lipids in renal cells, resulting in oxidative and endoplasmic reticulum stress, intracellular hypoxia, and inflammation, eventually leading to glomerulosclerosis and interstitial fibrosis. There is a growing body of evidence demonstrating that dysregulation of 5' adenosine monophosphate-activated protein kinase (AMPK), an enzyme that plays a principal role in cell growth and cellular energy homeostasis, in relevant tissues is a key component of the development of metabolic syndrome and type 2 diabetes mellitus; thus, targeting this enzyme may ameliorate some pathologic features of this disease. AMPK regulates the coordination of anabolic processes, with its activation proven to improve glucose and lipid homeostasis in insulin-resistant animal models, as well as demonstrating mitochondrial biogenesis and antitumor activity. In this review, we discuss new findings regarding the role of AMPK in the pathogenesis of DN and offer suggestions for feasible clinical use and future studies of the role of AMPK activators in this disorder.